2021
DOI: 10.1172/jci.insight.150861
|View full text |Cite
|
Sign up to set email alerts
|

Key molecular alterations in endothelial cells in human glioblastoma uncovered through single-cell RNA sequencing

Abstract: Glioblastoma is the most aggressive type of brain tumor with poor therapeutic response and prognosis. Passage of systemically delivered pharmacological agents into the brain is largely blocked by the blood-brain-barrier (BBB), an organotypic specialization of brain endothelial cells (EC). Tumor vessels in GBM are abnormal and more permeable, but the heterogeneity of BBB breakdown in different parts of the tumor vasculature and at the tumor's invasive front is largely unknown. Here, through single-cell RNA sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 35 publications
2
96
0
Order By: Relevance
“…Previous studies have shown that apln expression is highly expressed in endothelial tip cells, a type of endothelial cell found at the leading ends of sprouting vasculature that play a coordinating role in angiogenesis and vasculature organization in zebrafish (48,49). Furthermore, APLN has been shown to be expressed in sprouting vasculature, particularly in the context of injury or disease, in mice (50), and humans (51,52), indicating a conserved role for APLN across species. This scRNA-seq dataset presented here provides an atlas for the distinct transcriptional profiles of the cell types that comprise the adult zebrafish liver and establishes an important resource for utilizing zebrafish as a tool to study liver function and disease.…”
Section: Creation Of a Single Cell Atlas Of The Adult Zebrafish Livermentioning
confidence: 96%
“…Previous studies have shown that apln expression is highly expressed in endothelial tip cells, a type of endothelial cell found at the leading ends of sprouting vasculature that play a coordinating role in angiogenesis and vasculature organization in zebrafish (48,49). Furthermore, APLN has been shown to be expressed in sprouting vasculature, particularly in the context of injury or disease, in mice (50), and humans (51,52), indicating a conserved role for APLN across species. This scRNA-seq dataset presented here provides an atlas for the distinct transcriptional profiles of the cell types that comprise the adult zebrafish liver and establishes an important resource for utilizing zebrafish as a tool to study liver function and disease.…”
Section: Creation Of a Single Cell Atlas Of The Adult Zebrafish Livermentioning
confidence: 96%
“…This likely contributes to the poor T cell infiltration observed in GBM, as increased VEGF signaling in endothelial cells can reduce leukocyte recruitment by inhibiting the expression of adhesion molecules and chemokines required for T cell recruitment (28)(29)(30). Notably, vessel phenotype is heterogeneous in GBM and varies both between patients and within a single tumor (31). Single cell mRNA sequencing of endothelial cells isolated from human GBM demonstrated that while activated endothelial cells are detected in some patients, the majority of endothelial cells within the tumor are angiogenic and express low levels of adhesion molecules and chemokines (31).…”
Section: The Immune Microenvironment Of Gbmmentioning
confidence: 99%
“…Notably, vessel phenotype is heterogeneous in GBM and varies both between patients and within a single tumor ( 31 ). Single cell mRNA sequencing of endothelial cells isolated from human GBM demonstrated that while activated endothelial cells are detected in some patients, the majority of endothelial cells within the tumor are angiogenic and express low levels of adhesion molecules and chemokines ( 31 ).…”
Section: The Immune Microenvironment Of Gbmmentioning
confidence: 99%
“…Single cell RNA sequencing datasets of ECs from GBM and paired non-malignant control brain tissue were downloaded from the Gene Expression Omnibus (GEO) database (GSE162631). Information for cells and samples were obtained in the previous study (4). Only ECs from peripheral endothelial cell type I (Pe1), tumor core endothelial cell type I (Co1) and tumor core endothelial cell type II (Co2), which were represented in four patients, in the original study were selected for downstream analysis.…”
Section: Bioinformatics Analysis Of Ets1 Expression In Ecsmentioning
confidence: 99%
“…Microvascular proliferation and abnormal vasculature are the hallmarks of GBM (2,3). Endothelial cells (ECs) in GBM vessels are associated with a distinct gene signature characterized by upregulation of genes involved in basement membrane remodelling, cytoskeletal rearrangements, angiogenic sprouting and tip cell formation (4). Vascular abnormality aggravates GBM progression by promoting tumor cell invasiveness through inducing hypoxia (5,6).…”
Section: Introductionmentioning
confidence: 99%